A Key Work on German Philosophical Anthropology (KULT_online, 2010)
German Philosophical Anthropology commonly associated with Scheler, Plessner, and Gehlen is interpreted for the first time by the sociologist Joachim Fischer as an autonomous philosophical approach. It appears as an answer to the destruction of German classical Idealism during the nineteenth-century: while Idealists directly derived the Geist from subjectivity, Philosophical Anthropology constructs it "indirectly" (p. 519). Through non-reductionist comparative analysis of impulse life and biological forms of mankind, animal, and – in Scheler and Plessner – plant, each author of Philosophical Anthropology gives confirmation of and new definition to man's particular place (Sonderstellung). Fischer divides his work into two parts: in the first he masterfully reconstructs the history of Philosophical Anthropology by exploring both a considerable amount of sources and the institutional and historical contexts; in the second he elaborates its conceptual and methodological "identity core" (p. 575).